2017
DOI: 10.1115/1.4037325
|View full text |Cite
|
Sign up to set email alerts
|

Time-Response of Recent Prefilming Airblast Atomization Models in an Oscillating Air Flow Field

Abstract: The present study investigates the response of recent primary breakup models in the presence of an oscillating air flow, and compares them to an experiment realized by Müller and coworkers in 2008. The experiment showed that the oscillating flow field has a significant influence on the Sauter Mean Diameter (SMD) up to a given frequency. This observation highlights the low-pass filter character of the prefilming airblast atomization phenomenon, which also introduces a significant phase shift on the dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Hence, the discrepancy comes from the calibration constants. This model was already compared to an experiment similar to the present one in a previous publication (Chaussonnet et al 2017) and it was also found to deliver too small droplets. This is because in the bimodal PDF used by this model, one peak is overestimated compared to the other.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Hence, the discrepancy comes from the calibration constants. This model was already compared to an experiment similar to the present one in a previous publication (Chaussonnet et al 2017) and it was also found to deliver too small droplets. This is because in the bimodal PDF used by this model, one peak is overestimated compared to the other.…”
Section: Discussionmentioning
confidence: 60%
“…However, it predicts the current experiment with a remarkable good agreement. As pointed out in (Chaussonnet et al 2017), this can be explained by the fact that the model first overestimates the mean droplet size, and then reduces it by using the TAB model. The correlation from Eckel et al (2013) was calibrated using the experiment by Gepperth et al (2012).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other measurements by Müller et al [6] on a model planar atomizer showed that the droplet diameter responds almost proportionally to the air velocity fluctuations for excitation frequencies below 350 Hz. By taking the results from Müller a step further, Chaussonnet et al [7] used models to predict the volume probability density function and match the prediction to the experimental data obtained by means of shadowgraphy. In a more recent study, Su et al [8] attempted to incorporate experimental data obtained via Phase Doppler Anemometry (PDA) in empirical correlations for SMD predictions, in order to investigate the phase portraits of SMD versus gas velocity in a CFD simulation of a three-injector leanburn facility.…”
Section: Introductionmentioning
confidence: 99%